Assessment of seedling salinity tolerance of Bangladeshi coastal rice landraces using morpho-physiological stress indices - Somaddar, Uzzal; Mim, Sarah Khanam; Chandra Dey, Hridoy; Biswas, Ashish (Emirates Journal of Food and Agriculture, 2023)
Salt stress has detrimental effects on the growth and development of rice seedlings. In the present study we assessed salt-responsiveness of three coastal rice landraces namely Nona-morchi, Kalihytta and Nara. We conducted two factors pot trial that included five rice genotypes (three candidates coastal rice landraces, Binadhan-10 as tolerant check and BRRI dhan48 as sensitive check) against three salinity levels e.g., control (tap water), 6 and 12 dSm-1 of sodium chloride. Study revealed that, at 12 dSm-1 of salinity, Binadhan-10 showed the lowest reduction in shoot length (14.62%), shoot fresh weight (30.04%) and shoot dry weight (33.71%) which was followed by Nona-morchi, Kalihytta, Nara and BRRI dhan48. Two stress tolerance indices e.g., relative water content (RWC) and electrolyte leakage (EL), also support salt-induced responses of these five rice genotypes. At the highest level of salinity (12 dSm-1), the lowest RWC reduction was observed in Nona-morchi (8.20%) which is followed by Binadhan-10 (11.38%), Kalihytta (38.93%), BRRI dhan48 (36.30%) and Nara (36.51%). And, the highest EL increased in Nara (40.06%) which is followed by BRRI dhan48 (22.06%), Kalihytta (21.12%), Binadhan-10 (8.64%) and Nona-morchi (5.87%) compared with their respective controls. Importantly, photosynthetic pigments profile (chlorophyll a, chlorophyll b, total chlorophyll) were increased in Nona-morchi (24.48, 15.22 and 21.87%, respectively) and Binadhan-10 (13.75, 12.50 and 13.41%, respectively) and reduced in Kalihytta (7.89, 19.42 and 11.08%, respectively), Nara (27.76, 31.32 and 28.76%, respectively) and BRRI dhan48 (32.73, 36.97 and 34.02%, respectively) at 12 dSm-1 salinity compared with their respective controls. It is to noteworthy that at 6 dSm-1 of salt stress, shoot length significantly decreased in the sensitive check BRRI dhan48 by 23.07%, Kalihytta by 17.32% and Nara by 11.54%. While, no significant effect of 6 dSm-1 of salt stress was observed in Binadhan-10 and Nona-morchi in case of shoot length, root length, shoot fresh and dry weight, EL and RWC . Among the three coastal rice landraces, Nona-morchi found as highly tolerant and Kalihytta were found as moderately tolerant while Nara was identified as sensitive against salt stress (12 dSm-1). In the future, these identified salt tolerant rice genotypes might be the ideal resource for breeding new salt tolerant rice varietie